Distribution of heavy metals in soil and two plant species (Asystasia Coromandeliana and Phyllanthus Niruri) - Nur Anisa, Md. Jalil (Universiti Malaysia Sarawak, UNIMAS, 2008)
The pollution of the natural environment is and will remain forever, one of the important problems for the mankind. Two plant species namely Asystasia coromandeliana and Phyllanthus niruri were used to show the uptake of heavy metals from soil and distribution of heavy metals in their tissues samples. The analysis of Cd, Cr and Cu were carried out by using atomic absorption spectrophotometer (AAS). P. niruri had absorbed concentration of Cr and Cu in soil efficiently according to comparison between distribution of Cr and Cu in its root, stem and leaf with concentration of the heavy metals in soil. The same scale showed by A. coromandeliana, where the concentration of Cr and Cu uptake by its tissues samples was much higher and consistent than extraction of Cd. The high amounts of Cu and Cr distributed in tissues samples for both plant species were actually related to their potentials to uptake the heavy metals. Both of plants also showed the distribution of heavy metals was higher in root, followed by stem and leaf. The absorption of plants showed that P. niruri absorbed more Cr (103.66 mg/kg), followed by Cu (12.66 mg/kg) and Cd (12.60 mg/kg), whereas A. coromandeliana absorbed more Cu (112.28 mg/kg) and quite high of Cr (104.74 mg/kg), but absorbed only 4.9 mg/kg of Cd. The distribution pattern of heavy metals in these two plant species indicates that both of the plants are suitable as accumulator to absorb heavy metals from soil for remediation purposes.